Effect of aerobic exercise training on asthma control in postmenopausal women (the ATOM-study): protocol for an outcome assessor, randomised controlled trial - Ylva Hellsten; Vibeke Backer; Morten Hostrup; Erik Sören Halvard Hansen; Hanne Kruuse Rasmusen (BMJ Open)
Introduction Late-onset asthma in postmenopausal women is characterised by poor disease control with daily symptoms and reduced quality of life despite treatment with inhaled antiasthma therapies. These patients represent a phenotype that is characterised by low eosinophilic airway inflammation, severe symptoms, moderate obesity and poor response to inhaled antiasthma therapies, which highlights the need of identification of alternative treatment strategies. Thus, this study aims to evaluate if regular high-intensity aerobic exercise improves symptom control in postmenopausal women with asthma.Methods and analysis This is an ongoing randomised controlled trial planning to enrol 40 postmenopausal women with late-onset asthma. Participants are randomised 1:1 either to supervised exercise training (spinning) three times per week for 12 weeks or to usual care. The primary outcome is change from baseline to follow-up in the Asthma Control Questionnaire. Secondary outcomes are changes in markers of systemic inflammation, airway inflammation, body composition and right ventricular function of the heart.Ethics and dissemination The study is approved by the Ethics Committee in the Capital Region of Denmark nr. H-18028966 and the Danish Data Protection Agency nr. VD-2019–59. The methods used in the study are well known and have a low risk with a chance of substantial improvement in disease control in this patient group. Results are planned to be published in an international peer-reviewed medical journal regardless of outcome.Trial registration number NCT03747211.